Spatial Cross-Correlation of GOSAT CO2 Concentration with Repeated Heat Wave-Induced Photosynthetic Inhibition in Europe from 2009 to 2017 - Young-Seok Hwang; Stephan Schlüter; Jung-Sup Um (Remote Sensing, 2022)
In recent decades, European countries have faced repeated heat waves. Traditionally, atmospheric CO2 concentration linked to repeated heat wave-induced photosynthetic inhibition has been explored based on local-specific in-situ observations. However, previous research based on field surveys has limitations in exploring area-wide atmospheric CO2 concentrations linked to repeated heat wave-induced photosynthetic inhibition. The present study aimed to evaluate the spatial cross-correlation of Greenhouse gases Observing SATellite (GOSAT) CO2 concentrations with repeated heat wave-induced photosynthetic inhibition in Europe from 2009 to 2017 by applying geographically weighted regression (GWR). The local standardized coefficient of a fraction of photosynthetically active radiation (FPAR: −0.24) and the normalized difference vegetation index (NDVI: −0.22) indicate that photosynthetic inhibition increases atmospheric CO2 in Europe. Furthermore, from 2009 to 2017, the heat waves in Europe contributed to CO2 emissions (27.2–32.1%) induced by photosynthetic inhibition. This study provides realistic evidence to justify repeated heat wave-induced photosynthetic inhibition as a fundamental factor in mitigating carbon emissions in Europe.